Individual drivers and barriers to adoption of disease control and welfare practices in dairy and beef cattle production: a scoping review - Buchan, Marrissa S.; Lhermie, Guillaume; Mijar, Sanjaya; Pajor, Ed; Orsel, Karin (Frontiers in Veterinary Science, 2023)
The implementation of disease control and welfare practices is an essential part of limiting disease exposure in livestock, however successful adoption of these practices seem to be low in both the beef and dairy cattle industries. The main objectives of this scoping review were to characterize literature published exploring beef and dairy cattle producers’ perceptions on the implementation of various disease control and welfare practices, identify major themes of drivers and barriers that influence producers’ adoption of these practices, and identify current gaps in knowledge. A total of 2,486 articles were obtained from two database literature searches and screened, from which 48 articles published between 2010 and 2021 were deemed eligible and charted. Europe was the most common region for articles (58%). A majority of articles focused solely on dairy producers (52%). A wide range of barriers and drivers which were categorized into 4 and 5 key themes, respectively. The most commonly mentioned driver was animal health, welfare, and safety, while the most common barrier was costs. Potential gaps in literature were identified, including the underrepresentation of beef producer perceptions relative to dairy producers in current literature